Leaf Extract and Active Fractions of Dillenia pentagyna Roxb. Reduce In Vitro Human Cancer Cell Migration Via NF-κB Pathway - De, Debapriya; Chowdhury, Priyanka; Panda, Sujogya Kumar; Ghosh, Utpal (Integrative cancer therapies, 2022)
Background: Different parts of Dillenia pentagyna have long been used in traditional medicines to cure several diseases including cancer. However, the mechanism(s) of anti-cancer effects are still unknown. We aimed to elucidate the anti-metastatic potential of ethanolic extracts of leaves of D. pentagyna (EELDP) and active fractions of it in highly metastatic human cancer cells. Methods: We screened different HPLC fractions of EELDP based on their anti-metastatic effect. We used TLC and ESI-MS for determining the presence of various phytochemicals in EELDP and fractions. We monitored in vitro anti-metastasis effect of EELDP (0-0.6 mg/ml) and active fractions (0-0.050 mg/ml) on various human cancer cells like A549, HeLa, and U2OS. Results: EELDP significantly reduced cell viability and cell migration in A549, HeLa, and U2OS cells. However, higher sensitivity was observed in A549 cells. We screened 2 active HPLC fractions F6 and F8 having anti-MMPs activity. EELDP and active fractions reduced metastasis via the NF-κB pathway, decreased the expression of Vimentin, N-cadherin, and increased the expression of Claudin-1. Conclusion: Significant reduction of metastasis by EELDP at a dose of 0.1 mg/ml or by active fractions at 0.050 mg/ml implicates that the active compound(s) present in crude or fractions are extremely potent to control highly metastatic cancer.